Inflected and uninflected possessives and Lithuanian kienõ - de Vaan, Michiel (Baltistica, 2017)
It is argued that the uninflected possessive adjective Lithuanian kienõ ‘whose’ replaces an earlier form *kienè which arose from the addition of stressed -nè to monosyllabic *kie. As the source of the latter form, an innovation *kwo-iʔ ‘whose’ is posited, which was made as an uninflected adjective in *-iʔ to the interrogative pronoun. The model for this formation was the existence of Balto-Slavic *ʔmoiʔ ‘my’, *twoiʔ ‘your’, *swoiʔ ‘his, her own’, to which, according to a recent theory, the Proto-Slavic possessive adjectives *mojь, *tvojь, *svojь go back.